2014
DOI: 10.1111/cas.12554
|View full text |Cite
|
Sign up to set email alerts
|

Angiopoietin‐like protein 2 renders colorectal cancer cells resistant to chemotherapy by activating spleen tyrosine kinase–phosphoinositide 3‐kinase‐dependent anti‐apoptotic signaling

Abstract: Angiopoietin-like protein 2 (ANGPTL2) plays an important role in inflammatory carcinogenesis and tumor metastasis by activating tumor angiogenesis and tumor cell chemotaxis and invasiveness. However, it is unclear whether ANGPTL2 expression has an effect on tumor cell survival. Here, we explored that possibility by determining whether ANGPTL2 expression altered survival of human colorectal cancer cell lines treated with antineoplastic drugs. To do so, we generated SW480 cells expressing ANGPTL2 (SW480/ANGPTL2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 34 publications
1
23
0
Order By: Relevance
“…The predominant presence of Syk(L) as well as the reduction of both variants during apoptosis excluded the possibility of the role of Syk(S) and alternative splicing in colonocyte apoptosis. In this study, we suggest that Syk(L) is a pro‐survival factor for cultured colonocytes, which is consistent with a recently published report [Horiguchi et al, ]. However, clinical studies need to be carried out to confirm the role of Syk(L) in CRC progression.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The predominant presence of Syk(L) as well as the reduction of both variants during apoptosis excluded the possibility of the role of Syk(S) and alternative splicing in colonocyte apoptosis. In this study, we suggest that Syk(L) is a pro‐survival factor for cultured colonocytes, which is consistent with a recently published report [Horiguchi et al, ]. However, clinical studies need to be carried out to confirm the role of Syk(L) in CRC progression.…”
Section: Discussionsupporting
confidence: 92%
“…The pro‐survival signaling of Syk in epithelial cells is still under investigation, but activation of the PI3K/Akt pathway is a likely contributor [Geahlen, ]. Apoptosis is regulated through the intrinsic pathway by members of the Bcl‐2 family proteins [Wang et al, ] and Syk‐PI3K signals induced expression of this family genes to promote survival [Horiguchi et al, ]. Furthermore, Syk(L) affects the JNK signaling pathway, which in turn suppresses the expression of c‐JUN and its target genes, thereby inhibiting apoptosis and promotes cell survival [Prinos et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the higher efficiency of the lentivirus infection, we used the lentivirus infection to interfere with and overexpress ANGPTL2 protein[38]. The overexpression and knockdown of ANGPTL2 protein was satisfactory, with the confirmation of western blot for the sequential study.…”
Section: Discussionmentioning
confidence: 99%
“…Until recently, ANGPTL proteins were considered as orphan ligands, but some candidates have been proposed: the team of Oike and Tabata first hypothesized that Toll-like receptor 4 (TLR4) could be potential receptors for ANGPTL2 in endothelial cells and monocytes, since ANGPTL2 possesses a fibrinogen-like domain and that fibrinogen acts as an intrinsic TLR4 ligand [ 55 ]. The same team then demonstrated that integrin α 5 β 1 binds ANGPTL2 in adipocytes, endothelial cells, and cancer cells because the effects of recombinant ANGPTL2 protein were blocked by integrin α 5 β 1-neutralizing antibodies [ 5 , 26 , 63 ]. On the other hand, immune inhibitory receptor human leucocyte immunoglobulin-like receptor B2 (LILRB2) and its mouse orthologue-paired immunoglobulin-like receptor (PIRB) have been reported to bind several ANGPTL proteins, especially ANGPTL2 and ANGPTL5, in hematopoietic cells (HSC) [ 22 ].…”
Section: Putative Receptors Of Angptl2mentioning
confidence: 99%